Humanoid realistic simulator: The servomotor joint modeling - A. Paulo Moreira (2009)
Recent research in biped robots has resulted in a variety of prototypes that resemble their biological counterparts. Legged robots have several advantages, they can move in rugged terrains, they have the ability to choose optional landing points, and two legged robots are more suitable to move in human environment (Suzuki and Ohnishi, 2006). The simulator should capture the essential characteristics of the real system. In this paper, the servomotor model that powers the real humanoid joints is addressed. The model of a Dynamixel AX-12 servomotor and its characteristics are found by an iterative method based on a realistic simulator, the SimTwo (Costa, 2009). There are several simulators with humanoid simulation capability, like Simspark, Webots, MURoSimF, Microsoft Robotics Studio, YARP: Yet Another Robot Platform (Wang et al., 2006) and OpenHRP3 (Ope, 2009), meanwhile, the SimTwo, as a generic simulator, allows to simulate different types of robots and allows the access to the low level behaviour, such as dynamical model, friction model and servomotor model in a way that can be mapped to the real robot, with a minimal overhead. This simulator deals with robot dynamics and how it reacts for several controller strategies and styles. Using a realistic simulator can be the key for reducing the development time of robot control, localization and navigation software. It is not an easy task to develop such simulator due to the inherent complexity of building realistic models for the robot, its sensors and actuators and their interaction with the world (Browning and Tryzelaar, 2003). The purpose of developing such simulator is to produce a personalized and versatile tool that will allow the development and validation of the robots software thereby reducing considerably the development time. The paper is organized as follows: Initially, the real robot (which is the basis of the simulator) and its main control architecture are presented. Then, section 3 presents the developed simulator where the servomotor model was developed. Further, section 4 presents the validation of the simulator by comparing its results with the real robot. Finally, section 5 rounds up with the conclusions and future work.